Africa and International Relations in the 21st Century
XVII, 248 p.
Keywords: This book examines key emergent trends related to aspects of power, sovereignty, conflict, peace, development, and changing social dynamics in the African context. It challenges conventional IR precepts of authority, politics and society, which have proven to be so inadequate in explaining African processes. Rather, this edited collection analyses the significance of many of the uncharted dimensions of Africa's international relations, such as the respatialisation of African societies through migration, and the impacts this process has had on state power; the various ways in which both formal and informal authority and economies are practised; and the dynamics and impacts of new transnational social movements on African politics. Finally, attention is paid to Africa's place in a shifting global order, and the implications for African international relations of the emergence of new world powers and/or alliances. This edition includes a new preface by the editors, which brings the findings of the book up-to-date, and analyses the changes that are likely to impact upon global governance and human development in policy and practice in Africa and the wider world post-2015.